Do school inputs crowd out parents' investments in their children? - Birgitta Rabe (IZA World of Labor, 2019)
Many countries around the world are making substantial and increasing public investments in children by providing resources for schooling from early years through to adolescence. Recent research has looked at how parents respond to children's schooling opportunities, highlighting that public inputs can alternatively encourage or crowd out parental inputs. Most evidence finds that parents reduce their own efforts as schooling improves, dampening the efficiency of government expenditure. Policymakers may thus want to focus government provision on schooling inputs that are less easily substituted.
Keywords: I20; I24; 330; school inputs; parental investments; education production; input interactions